2007
DOI: 10.1111/j.1525-1470.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Fucosidosis: A Therapeutic Challenge

Abstract: Letters to the Editor are welcomed for publication (subject to editing). Letters must be signed by all authors, typewritten double spaced, and must not exceed two pages of text including references. Two copies of all letters should be submitted along with one copy on disk. Letters should not duplicate material submitted or published in other journals. Prepublication proofs will not be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…This classification is under debate since some studies suggest that the two types are actually a single disorder with signs and symptoms ranging only in severity. Life expectancy depends on the type and severity of the disease, with high mortality rates less than 10 years of age [6][7][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This classification is under debate since some studies suggest that the two types are actually a single disorder with signs and symptoms ranging only in severity. Life expectancy depends on the type and severity of the disease, with high mortality rates less than 10 years of age [6][7][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 100 cases of fucosidosis have been reported until now [1][2]. Deficiency of this enzyme leads to the accumulation of fucose-containing glycolipids and other substances in various organs, which display a wide array of symptoms, such as severe global developmental delay (95%), muscle stiffness (87%), coarse facies (79%), recurrent respiratory infections (78%), abnormal bone development (58%), tortuous conjunctival vessels (53%), clusters of enlarged blood vessels on the skin (52%), abnormal enlargement of visceral organs (44%), and seizures (38%) [3][4][5][6]. Studies have shown that around 60% of the patients die before the age of 10 years, secondary to recurrent pulmonary infections and neurological deterioration [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, while the two autosomal recessive conditions have a low prevalence, respectively, <1:1,000,000 for fucosidosis (<100 patients reported worldwide) (19) and 1:88,000 for MPS I (20), the frequency of the classic X-linked Fabry phenotype has been recently estimated to be at 1 in 40,000 male individuals and that of FD overall (classic and late onset) at 1 in 3100 newborn males screened in Italy (21) or 1 in 1250 Thai newborn males (22). However, while the two autosomal recessive conditions have a low prevalence, respectively, <1:1,000,000 for fucosidosis (<100 patients reported worldwide) (19) and 1:88,000 for MPS I (20), the frequency of the classic X-linked Fabry phenotype has been recently estimated to be at 1 in 40,000 male individuals and that of FD overall (classic and late onset) at 1 in 3100 newborn males screened in Italy (21) or 1 in 1250 Thai newborn males (22).…”
Section: Discussionmentioning
confidence: 99%
“…In the both families, two female subjects were double heterozygotes for Fabry and for fucosidosis or MPS I Hurler/Scheie, respectively. However, while the two autosomal recessive conditions have a low prevalence, respectively, <1:1,000,000 for fucosidosis (<100 patients reported worldwide) and 1:88,000 for MPS I , the frequency of the classic X‐linked Fabry phenotype has been recently estimated to be at 1 in 40,000 male individuals and that of FD overall (classic and late onset) at 1 in 3100 newborn males screened in Italy or 1 in 1250 Thai newborn males . Hence, the frequency of heterozygotes in the population for MPS I is calculated at 1:148 individuals, whereas for FD it should be around the double of the prevalence of the affected males.…”
Section: Discussionmentioning
confidence: 99%
“…Fucosidosis is an LSD caused by mutations in the FUCA1 gene, which is responsible for the production of L-fucosidase enzyme. 6,7 α-Mannosidosisis caused by the deficiency in the activity of the lysosomal enzyme α-mannosidase. 8 We have previously reported several tandem mass spectrometry (MS/MS)-based lysosomal enzymatic activity assays that use dried blood spots (DBS) collected from infants on newborn screening cards.…”
Section: Introductionmentioning
confidence: 99%